Edukasi dan Penyuluhan Pencegahan Anemia Pada Remaja Sebagai Upaya Peningkatan Kesehatan di SMAN 2 Ungaran - Khoirul Umam; Ayu Mega Pertiwi; Muhammad Dea Sabili; Any Asrhofah; Devi Mardiyanti (CANANG: Jurnal Pengabdian Masyarakat, 2026)
Anemia in adolescents remains a public health problem that impacts learning concentration, academic achievement, and the quality of adolescent health. Low knowledge about the importance of iron consumption and a healthy diet is one of the risk factors for anemia in adolescent girls. This community service activity aims to increase adolescent knowledge about anemia prevention through balanced nutrition education and the consumption of iron tablets (TTD). The implementation method is carried out through counseling using leaflets and interactive PowerPoint presentations with a lecture and discussion approach. The target of the activity is 50 students of SMA Negeri 2 Ungaran who were selected using a random sampling technique. Evaluation was carried out using a pre-test and post-test to measure the increase in participants' knowledge. The results showed an increase in participants' knowledge after being given education. The percentage of participants with very good knowledge category increased from 16% to 92%, while the sufficient category decreased from 4% to 0%. The average score of participants increased from 95.20 to 98.40 with a significance value of p 0.05 based on the Paired Sample t-test. Health education using leaflets and interactive presentations has proven effective in increasing adolescent knowledge about anemia prevention. This program is expected to support ongoing promotional and preventive efforts in the school environment